Numeracy Literacy Guidance Using Jarimatika Method on Students of Elementary School 1 Lamokato, Kolaka Regency, Southeast Sulawesi Province, Indonesia - Tri Maniarta Sari; Ernawati Ernawati; Irajuana Haidar; A.S. Alonemarera; Andi Saadillah (Universitas Mathla'ul Anwar Banten, 2022)
This guidance intends to provide guidance to class students of elementary school 1 Lamokato in using the Jarimatika method. This guidance is carried out because it is motivated by the low numeracy literacy of students at elementary school 1 Lamokato. This has an impact on the low ability of students to count. Therefore, guidance is needed for students using a different method from the method used by teachers at elementary school 1 Lamokato. This training was carried out from June to August 2022 at elementary school 1 Lamokato. The methods used in this training are demonstration methods, question and answer, and practice using the Jarimatika method. The students were very enthusiastic during the training. Students are interested in using the Jarimatika method. Students actively ask and answer about the Jarimatika method. Each student practices the method of Jarimatika in front of the class. The result of this training activity is that there is an increase in students' numeracy literacy in this case the ability to count.